The Impact of Principal Leadership on Teacher Quality and Performance: A Mixed-Methods Study in Deli Serdang Regency - Surbakti, Amanah; Siti Aisyah (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study examines the role of principal leadership in improving teacher quality and performance within the Siti Humairah Study Group in Deli Serdang Regency. Employing a mixed-methods approach, the research integrates quantitative data from surveys with qualitative insights gathered through interviews, observations, and document analysis. The findings reveal that principal leadership accounts for 44.2% of the variation in teacher quality and 60.4% of the variation in teacher performance, highlighting its significant impact. Effective leadership practices, such as strategic supervision, professional development facilitation, and participatory decision-making, were found to enhance teacher motivation and collaboration. However, challenges such as limited resources and disciplinary issues underscore the need for comprehensive interventions. The study emphasizes the importance of adaptive leadership styles tailored to contextual challenges. Successful principals created supportive environments, provided constructive feedback, and facilitated targeted training programs. Additionally, transformational and participatory leadership approaches were shown to foster teacher engagement and improve teaching quality. Nonetheless, external factors, including organizational culture and individual teacher attitudes, were found to moderate the effectiveness of leadership interventions. This research contributes valuable insights to the discourse on educational leadership and its influence on school effectiveness. It underscores the critical role of principal leadership in fostering teacher quality and performance while addressing persistent challenges. Practical implications include the need for strengthened leadership training programs and increased resource support to overcome operational and cultural barriers within schools. These recommendations aim to inform policymakers and educational leaders in driving sustainable improvements in teacher performance and student outcomes.